Unterlagen für eine Monographie der Saginae. III. Die Saginae der äthiopischen Region (Saltatoria: Tettigoniidae). - Kaltenbach, Alfred (Contributions to Entomology = Beiträge zur Entomologie, 1971)
The subfamily Saginae occurs in the Ethiopian region with three genera including 26 known species. Hemiclonia Kirby can maintained only as a subgenus of Clonia Stal. Cloniella was established as a new genus with Hemisaga praedatoria Distant as typus generis and Leptoclonia and Xanthoclonia were established as subgenera of the genus Clonia Stal. 11 species of the genus Clonia, one species of Cloniella and one species of Peringueyella were newly discovered. The special part of the paper contains keys and detailed diagnoses for alll genera, subgenera and species. In the final section an attempt is made to trace the chief directions of the spreading of the African Saginae by means of orthevolutiver trends.Nomenclatural ActsLeptoclonia Kaltenbach, 1971 (Clonia), sgen. n.turneri Uvarov, 1942 (Clonia), syn. n. of Clonia vittata (Thunberg, 1789)Xanthoclonia Kaltenbach, 1971 (Clonia), sgen. n.angolana Kaltenbach, 1971 (Clonia (Clonia)), spec. n.dewittei Kaltenbach, 1971 (Clonia (Clonia)), spec. n.intermedia Kaltenbach, 1971 (Clonia (Clonia)), spec. n.jagoi Kaltenbach, 1971 (Clonia (Clonia)), spec. n.kalahariensis Kaltenbach, 1971 (Clonia (Clonia)), spec. n.saussurei Kaltenbach, 1971 (Clonia (Clonia)), spec. n.uvarovi Kaltenbach, 1971 (Clonia (Clonia)), spec. n.zernyi Kaltenbach, 1971 (Clonia (Clonia)), spec. n.variabilis Kaltenbach, 1971 (Clonia (Clonia) wahlbergi), sspec. n.assimilis Kaltenbach, 1971 (Clonia (Hemiclonia)), spec. n.charpentieri Kaltenbach, 1971 (Clonia (Hemiclonia)), spec. n.minuta (Haan, 1842) (Clonia (Leptoclonia)), comb. n. hitherto Locusta (Saga) minutavansoni Kaltenbach, 1971 (Clonia (Leptoclonia)), spec. n.vittata (Thunberg, 1789) (Clonia (Leptoclonia)), comb. n. hitherto Locusta vittatatesselata (Saussure, 1888) (Clonia (Xanthoclonia)), comb. n. hitherto Clonia tesselatapraedatoria (Distant, 1892) (Cloniella), comb. n. hitherto Hemisaga praedatoriazambesica Kaltenbach, 1971 (Cloniella), spec. n.zulu Kaltenbach, 1971 (Peringueyella), spec. n.multispina Kaltenbach, 1971 (Peringueyella jocosa), sspec. n.Cloniella Kaltenbach, 1971 (Tettigoniidae), gen. n.